1992
DOI: 10.1002/cne.903240407
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural development of the medial superior olive (MSO) in the ferret

Abstract: When ferrets are born, four weeks before the onset of hearing, few synapses are evident in the medial superior olive (MSO). The synapses present are immature and almost exclusively found in the neuropil. The MSO somata are virtually devoid of synaptic contacts but are contacted by fine glial processes that increasingly ensheathe the somata during the first postnatal week. By P12, somatic synaptogenesis in the MSO is evident. Initially the terminals contain vesicles of irregular shape, size, and distribution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Thus, the degree of synaptic development in the ferret at the time of hearing would appear to be much more advanced than that in the quoll, although in the absence of counts of synaptic density in the ferret study such comparisons can only be inferred. Brunso-Bechtold et al (1992) did not describe synaptic development in the ferret during fetal life, but they note that very few synapses are present at birth. If the numbers of synapses are comparable to those early in pouch life in the quoll, it would suggest that synaptogenesis may be more protracted in the quoll than in the ferret and slower to peak in relation to hearing.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, the degree of synaptic development in the ferret at the time of hearing would appear to be much more advanced than that in the quoll, although in the absence of counts of synaptic density in the ferret study such comparisons can only be inferred. Brunso-Bechtold et al (1992) did not describe synaptic development in the ferret during fetal life, but they note that very few synapses are present at birth. If the numbers of synapses are comparable to those early in pouch life in the quoll, it would suggest that synaptogenesis may be more protracted in the quoll than in the ferret and slower to peak in relation to hearing.…”
Section: Discussionmentioning
confidence: 94%
“…Some information about hearing in this species has been published (Frost and Masterton, 1994;Muller et al, 1993;Willard, 19931, and there is a recent study of the ontogeny of brainstem evoked potentials in Monodelphis (Reimer, 1996). Brunso-Bechtold et al (1992) consider that the few synapses present at birth in ferrets are likely sites of synaptic transmission, but this is more debatable in quolls in the first few weeks of life, which are much less mature generally than ferrets at birth. Synaptic contacts at this age in quolls feature very few vesicles, are made on neuropil, and are probably related to circuits intrinsic to the IC.…”
Section: Discussionmentioning
confidence: 95%
“…hearing onset (around P28; Moore, 1982) and during the period of synaptogenesis (Brunso-Bechtold et al, 1992). Moreover, electrophysiological studies in fetal rats have identified functional glycinergic neurotransmission in the SOC as early as embryonic day 18, i.e., 4 days before birth and, therefore, in the absence of a1-containing GlyRs (Kandler and Friauf, 1995).…”
Section: Development Of A1 Glyrs In the Auditory Brainstemmentioning
confidence: 99%
“…Parvalbumin is present at birth in the region where highfrequencies will be represented, and calbindin, where low frequencies will be represented. However, this transient postnatal pattern diminishes within the first two postnatal weeks in apparent synchrony with rapid synapse proliferation in the superior olive (2 weeks postnatal, Brunso-Bechtold et al, 1992), and eventually parvalbumin is found in all or most principal cells in the adult LSO. A number of anatomical and functional features also develop from medial to lateral in the LSO, including expression of glycine receptors , axonal (Sanes and Siveris, 1991) and dendritic maturation (Sanes et al, 1992), and synaptic integration (Sanes, 1993) in gerbil.…”
Section: Discussionmentioning
confidence: 97%
“…6B). In postnatal-day 14 and older ferrets, after the approximate time when somatic synapses proliferate in the ferret superior olive (e.g., Brunso-Bechtold et al, 1992), calbindin-positive endings formed a cobbled network covering the somata of the principal cells in both the LSO (Fig. 7A) and the MSO (not shown, see Fig.…”
Section: Calbinin-immunopositive Cells In the Socmentioning
confidence: 97%